A vision of Africa's future Mapping change, transformations and trajectories towards 2030 - Carbone, Giovanni (Pubblicazioni ISPI, 2018)
Africa is a fast-changing continent and an area of rising global relevance, where major transformation processes are currently underway, from demographic expansion to economic development, from social progress to environmental challenges, from technological innovation to continental integration, from political change to migratory pressures. How will these complex transformations shape the Africa of tomorrow?This Report sets out a vision for Africa's future based on five key traits: an archipelago of heterogeneous growth trajectories; the revolutionary impact of technological leapfrogging; regional integration and the growing role of sub-regional processes; the clustering of instability mainly around the core of the region; and the migration movements that originate from - but also predominantly remain within - the African continent.